The Kairos document - challenge to the church: a theological comment on the political crisis in South Africa - Kairos Theologians (Journal of Theology for Southern Africa, 1985)
The Kairos document is a Christian, biblical, and theological commen ton the political crisis in South Africa today. It is an attempt by concerned Christians in South Africa to reflect on the situation of death in our country. It is a critique of the current theological models that determine the type of activities the Church engages in to try to resolve the problems of the country. It is an attempt to develop, out of this perplexing situation, an alternative biblical and theological model that will in turn lead to forms of activity that will make a real difference to the future of our country. [excerpt fr preface].
Keywords: Church and state – Africa; Civil rights – South Africa; Government; Resistance to; Justice – Biblical teaching; Reconciliation; Repression; South Africa – Church history – 1961-1994; South Africa – Politics and government; South Africa – Race relations; Theology – South Africa; Violence